Differences in ocular parameters between diurnal and nocturnal raptors. (18th November 2013) - Beckwith‐Cohen, Billie; Horowitz, Igal; Bdolah‐Abram, Tali; Lublin, Avishai; Ofri, Ron
Abstract: Objective: To establish and compare normal ocular parameters between and within diurnal and nocturnal raptor groups. Animals studied: Eighty‐eight ophthalmically normal raptors of six nocturnal and 11 diurnal species were studied. Procedure: Tear production was measured using Schirmer tear test (STT) and phenol red thread test (PRTT), and applanation tonometry was conducted. Ultrasonographic measurements of axial length (AL), mediolateral axis (ML), vitreous body (VB), and pecten length (PL) were recorded, and conjunctival cultures were obtained. Results: A weak correlation ( R  =   0.312, P  =   0.006) was found between PRTT and STT. Tear production was significantly lower in nocturnal species ( P  <   0.001), but no difference was observed in intraocular pressure (IOP). VB and PL were significantly longer in diurnals ( P  <   0.001 and P  =   0.021, respectively), and no significant difference was observed in AL and ML. When comparing results within these groups, there was a significant difference between most species for all parameters except IOP. Fifty‐one percent of the examined raptors were positive for mycology or bacteriology, either on culture or PCR. The most common infectious agent isolated was Staphylococcus spp. Conclusions: Phenol red thread test and STT are both valid methods to measure tear production; however, a separate baseline must be determined for each species using these methods, as the results of one method cannot be extrapolated to the other. Due to significant differences observed within diurnal and nocturnal species, it appears that a more intricate division should be used when comparing these parameters for raptors, and the classification of diurnal or nocturnal holds little significance in the baseline of these data.